JOB SATISFACTION AND EMPLOYEE PERFORMANCE FACTORS IN PALM OIL PLANTATIONS - Damai, Prasis; Rofiaty, Rofiaty; Sudjatno, Sudjatno (Jurnal Aplikasi Manajemen, 2023)
The research objective was to determine the effect of organizational culture, compensation, and motivation on job satisfaction and employee performance of oil palm plantations at Katari Agro Estate, PT. Bumitama Gunajaya Agro, Central Kalimantan Province. The research sample of 200 plantation direct employees was selected by accidental sampling method from 428 populations. Data were collected using a questionnaire and then analyzed by variant-based Structural Equation Model (SEM) or Partial Least Square (PLS). The results of the analysis prove that organizational culture, compensation, and motivation directly have a significant effect on job satisfaction. Organizational culture, compensation, and motivation have a significant direct effect on employee performance. Job satisfaction directly has a significant effect on employee performance. The indirect effect between organizational culture and motivation on performance through job satisfaction is not significant. The indirect effect between compensation on performance through job satisfaction has significant. The study results have implications for organizational culture, compensation, and employee motivation that need to be improved to increase job satisfaction and employee performance. Suggestions for further research include exploring research by adopting qualitative studies to explain the symptom further and focusing on the influence of organizational culture, compensation, and motivation on indirect employee or managerial employee groups.